Voltage-gated potassium channels and genetic epilepsy - Zheng, Yiting; Chen, Jing (Frontiers in Neurology, 2024)
Recent advances in exome and targeted sequencing have significantly improved the aetiological diagnosis of epilepsy, revealing an increasing number of epilepsy-related pathogenic genes. As a result, the diagnosis and treatment of epilepsy have become more accessible and more traceable. Voltage-gated potassium channels (Kv) regulate electrical excitability in neuron systems. Mutate Kv channels have been implicated in epilepsy as demonstrated in case reports and researches using gene-knockout mouse models. Both gain and loss-of-function of Kv channels lead to epilepsy with similar phenotypes through different mechanisms, bringing new challenges to the diagnosis and treatment of epilepsy. Research on genetic epilepsy is progressing rapidly, with several drug candidates targeting mutated genes or channels emerging. This article provides a brief overview of the symptoms and pathogenesis of epilepsy associated with voltage-gated potassium ion channels dysfunction and highlights recent progress in treatments. Here, we reviewed case reports of gene mutations related to epilepsy in recent years and summarized the proportion of Kv genes. Our focus is on the progress in precise treatments for specific voltage-gated potassium channel genes linked to epilepsy, including KCNA1, KCNA2, KCNB1, KCNC1, KCND2, KCNQ2, KCNQ3, KCNH1 and KCNH5. This article focuses on summarizing recent clinical developments concerning the critical voltage-gated potassium (KV) family-related epilepsies from the KCNA-, KCNB-, KCNC-, KCND-, KCNQ-and KCNH-subfamilies.